Impoverishing Corruptors or Just a Slogan? The Disparity in Asset Confiscation Policies Between Indonesia and Singapore - Andi Reski Tenripada Mannan; Muhammad Fachri Said; Moch Andry Wikra Wardhana Mamonto (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze and compare criminal law policies related to the confiscation of assets resulting from corruption in Indonesia and Singapore, and to identify obstacles and solutions that can be implemented in Indonesia. The method used is normative legal research with a comparative approach, through a review of laws and regulations, doctrines, and legal practices in both countries. The results of the study indicate that Indonesia still faces a legal vacuum because it does not yet have a comprehensive Non-Conviction Based (NCB) Asset Forfeiture regulation, in contrast to Singapore, which has implemented it effectively through the Corruption, Drug Trafficking and Other Serious Crimes (Confiscation of Benefits) Act (CDSA) since 1992. In addition, there are four main obstacles in Indonesia, namely the non-passage of the Asset Forfeiture Bill, the absence of a mechanism for reversing the burden of proof, regulatory fragmentation, and weak coordination between law enforcement agencies. Based on these findings, this study recommends accelerating the ratification of the Asset Forfeiture Bill, harmonizing regulations, strengthening institutional independence, and adapting best practices from Singapore into the national legal system